Demokrasi Pendidikan pada Tataran Makro dan Mikro - Suluh, Melkiansu; Bitu, Yuliana Sesi (CT. Rajawali media Utama, 2023)
Covid-19 is the SARS-COV virus that has attracted the attention of many people, including the Indonesian government. This slow virus has since become a panic-inducing pandemic. Various information spread and the increasing number of fatalities has an impact on various social situations. Covid-19 does not only have an impact on health aspects but paralyzes every aspect of people's lives. The magnitude of the influence of the Covid-19 virus gave birth to various social phenomena among the community. Anxious and fearful attitudes have influenced people's mindsets and ways of acting. Covid-19 has given rise to new social phenomena, ranging from anti-social behavior to various efforts made by the community in fighting COVID-19. There are various scientific, non-scientific, to spiritual practices carried out by the community with the aim of avoiding the Covid-19 virus. Based on the social situation, this paper seeks to examine the critical attitude of society towards social phenomena in the reflection of the philosophy of science. The method used to study this phenomenon is the literature study method. Based on the study, it was argued that society needs to address various social phenomena critically and responsibly so that the decisions taken are not biased and do not have a negative impact on social life. A critical attitude is needed in filtering various circulating people's mindsets and ways of acting. Covid-19 has given rise to new social phenomena, ranging from anti-social behavior to various efforts made by the community in fighting COVID-19. There are various scientific, non-scientific, to spiritual practices carried out by the community with the aim of avoiding the Covid-19 virus. Based on the social situation, this paper seeks to examine the critical attitude of society towards social phenomena in the reflection of the philosophy of science. The method used to study this phenomenon is the literature study method. Based on the study, it was argued that society needs to address various social phenomena critically and responsibly so that the decisions taken are not biased and do not have a negative impact on social life. A critical attitude is needed in filtering various circulating information so that you don't become a victim of misinformation. Every decision taken must be made critically so that it is beneficial and has a positive effect on social life.